Pengaruh Digital Marketing Dan Kualitas Produk Terhadap Minat Beli Ms Glow Pada Masa Pandemi ( Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2018 ) - Milda Olivia; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The condition of the State of Indonesia is currently experiencing a crisis that is quite worrying. The emergence of COVID-19 which is busy in various parts of the world has had a negative impact on various sectors of the country. One of them is in the field of the country's economy. The use of cosmetics and other beauty care activities is also decreasing because people are more often at home. In addition to avoiding the transmission of the corona virus, various economic problems have also become a reason for people to temporarily leave the beauty treatment ritual that costs quite a lot. The skin is the outermost and widest defense organ of the human body so it is important to maintain its health. This is the reason people use beauty products more regularly in order to maintain the health of their skin. In addition, the increased use of skincare products can be seen based on the results of interviews with sellers of MS Glow products. Sales of MS beauty cosmetics are 50 percent compared to before the pandemic. The purpose of this study was to determine digital marketing and product quality simultaneously on interest in buying Ms Glow's products during the pandemic. The population in the study were active students of FEB 2018 Islamic University Malang and users of Ms Glow products. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 65 respondents. The results of the research show that partially digital marketing and product quality have a significant effect on buying interest. Meanwhile, simultaneously digital marketing and product quality have a significant effect on buying interest. Keywords: Digital Marketing, Product Quality and Buying Interest.